Prioritizing potential circRNA biomarkers for bladder cancer and bladder urothelial cancer based on an ensemble model - Su, Qiongli; Tan, Qiuhong; Liu, Xin; Wu, Ling (Frontiers in Genetics, 2022)
Bladder cancer is the most common cancer in the urinary system. Bladder urothelial cancer accounts for 90% of bladder cancer. The two cancers have high morbidity and mortality rates worldwide. The identification of biomarkers for bladder cancer and bladder urothelial cancer helps their diagnosis and treatment. CircRNAs are considered oncogenes or tumor suppressors in cancers and play important roles in the occurrence and development of cancers. In this manuscript, we developed an Ensemble model, CDA-EnRWLRLS, to predict CircRNA-Disease Associations (CDA) combining Random Walk with restart and Laplacian Regularized Least Squares and further screen potential biomarkers for bladder cancer and bladder urothelial cancer. First, we compute disease similarity by combining the semantic similarity and association profile similarity of diseases and circRNA similarity by combining the functional similarity and association profile similarity of circRNAs. Second, we score each circRNA-disease pair by random walk with restart and Laplacian regularized least squares, respectively. Third, circRNA-disease association scores from the above models are integrated to obtain the final CDAs by the soft voting approach. Finally, we use CDA-EnRWLRLS to screen potential circRNA biomarkers for bladder cancer and bladder urothelial cancer. CDA-EnRWLRLS is compared to three classical CDA prediction methods (CD-LNLP, DWNN-RLS, and KATZHCDA) and two individual models (CDA-RWR and CDA-LRLS) and obtains better AUC of 0.8654. We predict that circHIPK3 has the highest association with bladder cancer and may be its potential biomarker. And circSMARCA5 has the highest association with bladder urothelial cancer and may be its potential biomarkers.